"As Good As It Gets"1: Undocumented Latino Day Laborers Negotiating Discrimination in San Francisco and Berkeley, California, USA. (April 2014) - QUESADA, JAMES; ARREOLA, SONYA; KRAL, ALEX; KHOURY, SAHAR; ORGANISTA, KURT C.; WORBY, PAULA
Abstract Undocumented Latino day laborers in the United States are vulnerable to being arrested and expelled at any time. This social fact shapes their everyday lives in terms of actions taken and strategies deployed to mitigate being confronted, profiled, and possibly incarcerated and deported. While perceptions of threat and bouts of discrimination are routine among undocumented Latino day laborers, their specific nature vary according to multiple social factors and structural forces that differ significantly from locale to locale. The experience of discrimination is often tacitly negotiated through perceptions, decisions, and actions toward avoiding or moderating its ill effects. This essay examines urban undocumented Latino day laborers over a variety of sites in the greater San Francisco Bay Area, which, compared to many metropolitan areas in the U.S. is "as good as it gets" in terms of being socially tolerated and relatively safe from persecution. Nonetheless, tacit negotiations are necessary to withstand or overcome challenges presented by idiosyncratic and ever changing global, national/state, and local dynamics of discrimination.